Oral Metformin Treatment Prevents Enhanced Insulin Demand and Placental Dysfunction in the Pregnant Rat Fed a Fructose-Rich Diet. (16th August 2012) - Alzamendi, Ana; Del Zotto, Hector; Castrogiovanni, Daniel; Romero, Jose; Giovambattista, Andres; Spinedi, Eduardo
Abstract : The intake of a fructose-rich diet (FRD) in the normal female rat induces features similar to those observed in the human metabolic syndrome phenotype. We studied the impact of FRD administration to mothers on pregnancy outcome. On gestational day (Gd) zero rats were assigned to either group: ad libitum drinking tap water alone (normal diet, ND) or containing fructose (10% w/vol; FRD) through pregnancy; all rats were fed a Purina chow diet ad libitum ND and FRD rats were daily cotreated or not with metformin (60 mg/Kg/day oral; ND + MF and FRD + MF) and submitted to a high glucose load test on Gd 14. Additionally, placentas from different groups were studied on Gd 20. Data indicated that: (1) although FRD rats well tolerated glucose overload, their circulating levels of insulin were significantly higher than in ND rats; (2) the mesometrial triangle blood vessel area was significantly lower in placentas from FRD than ND dams; (3) the detrimental effects of FRD administration to mothers were ameliorated by metformin cotreatment. Our study suggests that excessive intake of fructose during pregnancy enhanced the risk for developing gestational diabetes and subsequent preeclampsia, and that metformin prevented the poor pregnancy outcome induced by FRD.